Type of setting for the inpatient adolescent with an eating disorder: Are specialized inpatient clinics a must or will the pediatric ward do? - Akgül, Sinem; Pehlivantürk-Kızılkan, Melis; Örs, Sine; Derman, Orhan; Düzçeker, Yasemin; Kanbur, Nuray (The Turkish Journal of Pediatrics, 2016)
There are a range of different services for treating adolescent eating disorders (ED) but there is no clinical consensus and a paucity of research indicating which type of treatment setting is the best. Although it would be ideal to have a specialized ward for these patients what happens when this is not possible? The aim of this study was to evaluate patients with ED hospitalized on a general pediatric ward. A retrospective chart review for 37 patients hospitalized for an ED and followed by a team consisting of an adolescent medicine specialist, a child and adolescent psychiatrist and a dietician on a pediatric ward were re-evaluated. Twenty-four (64.9%) patients were diagnosed with anorexia nervosa (AN) restricting type, 8 (21.6%) with anorexia nervosa binging purging type, 3 (8.1%) with bulimia nervosa (BN) and 2 (5.4%) with eating disorder otherwise not specified. The mean age at admission was 14.79 ± 1.75 years and 7 (20%) were males. A majority were hospitalized due to medical instability. Mean period of time from admittance to medical stabilization was 6.04 ± 4.79 days. The mean period of admittance was 26.4 ± 11.9 days for AN and 23.7 ± 15.03 days for BN patients. The mean calorie intake of the AN group was 607 ± 333 kcal and 2,358 ± 605 kcal at hospitalization and discharge, respectively. Hypophosphatemia occurred in 2 patients during refeeding. Mean total weight gained during the whole hospitalization period was 3,950 ± 3,524grs. This study shows that although not ideal, EDs can successfully be followed on general pediatric wards and could have implications at centers with no specialized wards.
Keywords: admission; adolescents; clinical setting; eating disorder